The use of digital technologies for the teaching of Astronomy: a systematic review of literature (Research, Society and Development, 2019)
The Digital Information and Communication Technologies are instruments that can aid the process of teaching and learning of contents that are often abstract, such as the astronomical concepts that in many cases happen in a confusing way and are even excluded from the science syllabus, making the teaching of astronomy incoherent with the student reality. Thus, the present work had the objective of investigating, through a Systematic Review of Literature (RSL), which are the digital technologies that are being used for the teaching of astronomy in the school context and what are the main astronomical contents taught through these technologies. The RSL was the methodological approach adopted for this exploratory study, which had the search interval from 2000 to 2017, in the following databases: the Theses and Dissertations Bank of the Coordination of Improvement of Higher Level Personnel, the Digital Library Brazilian Journal of Theses and Dissertations, the annals of the National Symposium on Astronomy Education, the annals of the National Meeting of Research in Science Education, and the journals listed in the restricted index in the Teaching area of the Sucupira Platform. As results, of the 19.053 papers analyzed, only 33 addressed the thematic, being that the majority of them used the Softwares as a technological instrument to teach astronomical contents. In addition, the results showed that the content “Solar System” corresponds to the most taught through digital technologies in schools. Therefore, the results point that there are few researches that indicate the use of technological resources for the teaching of Astronomy.